Teaching management: a view from organizational theories and pedagogy - Avila Guerrero, Flor Marlén (Universidad Pedagógica y Tecnológica de Colombia, 2011)
With a view to the progress in the development of knowledge in the area of administration, is intended to give a first look at a review on the various contributions on the subject arise. Therefore in this document is intended to travel through the conceptualization of government from the organizational and pedagogical and therefore is presented in four parts: the first relates to a review of the concept of administration, how addresses the administrative and organizational theories, the second gives an account of the pedagogy of teaching management in the third presents a discussion on the literature review conducted, which reveals a number of concerns that provide elements for the formulation research projects and finally show some points of arrival as opening the way to new perspectives and approaches on the subject.